EXTENSÃO DA VIDA DE PRATELEIRA DE OVOS PARA CONSUMO PELA COBERTURA COM FÉCULA DE MANDIOCA - FERNANDES, Eduardo Dionísio; GARCIA, Elis Regina de Moraes; SANCHES, Danilo de Souza; ÁVILA, Laura Ramos de; FRANCO, Roberto Henrique Serra; REICHEL, Dieimes Vilela (ANAIS DO ENIC, 2017)
-